Burning forests: the wood pellet industry’s framing of sustainability and its shadow places - Kinefuchi, Etsuko (Frontiers in Communication, 2024)
Woody biomass energy has exponentially grown in the last decade as a renewable energy alternative to fossil fuels. The growing trend of burning trees amid global climate crisis suggests that the wood pellet industry has been grossly successful in positioning itself as a sustainability leader. What communicative frames has the industry harnessed to communicate sustainability? What discursive strategies has the industry adopted to position itself as a global sustainability leader? This paper examines the woody biomass industry's construction of sustainability by focusing on the case of the world's largest wood pellet company, Enviva. Following ecolinguistics, the first part of the paper discusses the frames that Enviva engages to communicate its sustainability. Then, the discussion turns to the spheres of life that Enviva omits from its framing but are crucial to the conceptualization of sustainability from the point of view of ecojustice. Ultimately, the paper calls for the consideration of life on land from an ecojustice perspective. Analytical Framework: Ecolingustics, Framing, and Greenwashing Ecolinguistics is a distinct theoretical movement in linguistics to recognize and account for language and language-users as being situated in not only sociocultural and cognitive spaces but also physical and natural spheres (Chen 2016). Language is part of the ecological world, and it shapes and is